Clinical usefulness of ramucirumab plus paclitaxel for unresectable and recurrent gastric cancer - Hayase, Suguru (Fukushima J Med Sci, 2019)
INTRODUCTION: Recently in Japan, Ramucirumab (RAM) became the first anti-angiogenic agent to be approved for second-line treatment of gastric cancer. In the present study, we aimed to evaluate the efficacy and safety of RAM plus paclitaxel (PTX) in patients with unresectable and recurrent gastric cancer in our institution. PATIENTS AND METHODS: The subjects were 11 patients with unresectable and recurrent gastric cancer who received RAM plus PTX as a second- or later-line treatment at our hospital between June 2015 and September 2017, after the failure of previously-attempted treatments. We assessed the efficacy and safety of RAM plus PTX, and also compared them between patients aged <75 years (n=6) and those aged ≥75 (n=5), by performing a retrospective analysis based on the data obtained from daily clinical practice for gastric cancer treatment. RESULTS: Objective tumor response was observed in one of the 11 patients (9.1%) with partial response, and disease control was seen in the remaining 10 (90.9%). The median overall survival (OS) and progression-free survival (PFS) of the patients were 20.8 months (95% CI 7.8-NA (not applicable)) and 11.3 months (95% CI 6.5-NA), respectively. There were no serious adverse events. The median OS for the <75 years group and ≥75 years group was NA (due to short follow-up period) and 20.8 months (p = 0.336), respectively, and their respective median PFS rates were 9.4 and 11.3 months (p = 0.492). The difference of rate of adverse events was not significant between the two age groups in the present study, though the number of adverse events was not sufficient. CONCLUSION: The results of the present study suggest that the combination chemotherapy of RAM and PTX was effective in unresectable and recurrent gastric cancer patients as a second- or later-line therapy, and has been shown to be safe and feasible in elderly patients.